Diplomatic Service of Italian Diplomat J.-C. de Ludolf (1805–1861) - R. O. Reinhardt (Научный диалог, 2021)
The issue of periodization and  establishment of chronological frames of  the  stages of the diplomatic service of J.-C. de Ludolf, who represented the Kingdom of Naples abroad from 1805, and after its unification with the Sicilian Kingdom in 1816 and un  til the abolition  in  1861  —  the  Kingdom  of the Two Sicilies. It is shown that, despite Ludolf's many years of work in the Russian direction in various qualities, the coverage of the role and place of his figure in foreign policy processes is very fragmentary in Russian historiography. With the aim of the initial reconstruction of the key milestones in the diplomatic career of this historical person, study of foreign sources: materials from the State Archives of Naples, the memoirs of his daughter, as well as biographical works was carried out. By analyzing and systematizing the information presented in them, four periods of Ludolf's diplomatic activity are highlighted and briefly characterized. His most important achievements at each of the respective stages are outlined, while it is noted that a long stay in the service line in the Russian Empire at least had a significant impact on the professional development of a diplomat. It was revealed that St. Petersburg became the first and last point of his career path, during which he managed to work there as an attaché, plenipotentiary envoy and ambassador-at-large.